EFFICIENCY IN WRITING SOFTWARE WITH VIM - Coimbra de Oliveira, Bruno; Zuchi, Jederson Donizete (Revista Interface Tecnológica, 2020)
Modal editing is a, nowadays rare, concept that offers multiple interaction modes which are optimized for specific types of actions and interactions within a text editor. This study aimed to provide insight on the pros and cons of using a nowadays considered “outdated” piece of software called Vim for daily usage, and how its rationale helps its users to realize their objectives in an efficient and powerful manner. Furthermore, a test case with several subjects was put into place to gauge exactly how Vim compares to a standard editor on a particular scenario with timed comparison, following up on an analysis that was made based on the results of that experiment. Ultimately, it was concluded that, even for an old-fashioned tool, when certain criteria were met, Vim still posed as a strong contender for automating repetitive tasks, performing considerably faster than its adversaries. This experiment also served as a motive to demonstrate what might be gained from a tool with such a difficult learning curve.